26. ĐÁNH GIÁ KẾT QUẢ ĐẶT BUỒNG TIÊM DƯỚI DA DƯỚI HƯỚNG DẪN CỦA SIÊU ÂM VÀ HIỆU QUẢ SỬ DỤNG TẠI BỆNH VIỆN UNG BƯỚU THÀNH PHỐ CẦN THƠ (Tạp chí Y học Cộng đồng, 2025)
Subject and methods: A prospective cross-sectional descriptive study of 51 cancer patients who underwent ultrasound-guided subcutaneous port chamber implantation between April 2024 and December 2024 at Can Tho City Oncology Hospital was conducted.Objective: Evaluate the results of performing the procedure of placing a subcutaneous injection chamber under ultrasound guidance and the effectiveness of using chemotherapy for cancer patients.Subjects and methods: Cross-sectional prospective study of 51 cancer patients, placed in an infusion chamber under ultrasound guidance from April 2024 to December 2024 at Can Tho Oncology Hospital.Results: Female/male ratio was 9.2/1, average age was 53.33 years old. The average procedure time was 30 minutes, with 68.6% of catheters placed in the right internal jugular vein. The successful placement rate in 1 needle puncture under ultrasound was 98%, in 1 case a second needle puncture was required because the venous malformation could not be proactively identified before the procedure. Complication rate was 2%, no late complications were recorded. After an average follow-up of 4.24 months, 98% of patients were satisfied with the effectiveness of using the injection chamber.Conclusions: Placing the subcutaneous injection chamber under ultrasound guidance is a safe procedure with few complications, not only achieving patient satisfaction but also improving the patient’s quality of life when used in chemotherapy. The subcutaneous injection chamber should be placed under ultrasound guidance into the right internal jugular vein site for cancer patients.
Keywords: Buồng tiêm dưới da; hướng dẫn của siêu âm; tĩnh mạch cảnh trong; hóa trị